Teacher attrition in the State of Kansas, 2018-2019 - Lam, Chanh Bao (Kansas State University, 2021)
One key determinant of the stability and the progress of an educational system is its teacher workforce. However, in the State of Kansas, teacher shortage has consistently been a problem over the past five years. As the state’s task force on teacher vacancy and supply emphasized, teacher attrition had been and would continue to be a contributor to this shortage. Since teacher attrition is unique to each state, a study that specifically examines the turnover factors associated with Kansas teachers is now more than necessary. Using data from the Kansas Educator Data Collection System and the National Center for Educational Statistics, this study firstly examines the overall pattern of Kansas teacher attrition and the average patterns within a Kansas school, district, county, and region. Secondly, the study examines specific forms of teacher attrition including transferring among schools within the state, switching to a school out of the state, and leaving the teaching profession. Lastly, the study examines particular patterns of teacher attrition in specific Kansas’s geographical regions, including the North East, North Central, North West, South East, South Central, and South West. Statistically significant results show that teachers’ employment status, years of experience in the teaching profession and the current school districts, academic qualification, and Kansan education backgrounds are associated with their mobility decisions. Moreover, findings suggest that school’ economic status and student body’s characteristics are correlated to teacher attrition. Furthermore, external factors including salary and the unique characteristics of the local geographical region are found influential to teacher turnover. Deriving from the study’s most robust findings, recommendations for teacher policies in Kansas are suggested.
Keywords: Kansas; Teacher attrition; Teacher retention; Teacher vacancies; Teacher policies